Effect of the formation temperature of the AlN/Si interface on the vertical-direction breakdown voltages of AlGaN/GaN HEMTs on Si substrates. Issue 50 (8th June 2016) - Yamaoka, Yuya; Ito, Kazuhiro; Ubukata, Akinori; Tabuchi, Toshiya; Matsumoto, Koh; Egawa, Takashi
ABSTRACT: In this study, the initial AlN layer and the vertical-direction breakdown voltage (VDBV) of AlGaN/GaN high-electron-mobility transistors (HEMTs) were characterized. Prior to the formation of the interface between the AlN layer and the Si substrate, only trimethylaluminum (TMA) was introduced without ammonia to control the crystal quality of initial AlN layer (TMA preflow). HEMT structures were simultaneously grown on identical AlN layers on Si substrates (AlN/Si templates) grown using different TMA preflow temperatures. The density of screw- or mixed-type dislocations in the initial AlN layer decreased as the TMA preflow temperature increased. Further, the VDBV of the HEMT structure increased as the TMA preflow temperature increased. It is supposed that the screw- or mixed-type dislocations are the possible source of the vertical leakage current in the HEMT structures. The improvement in the crystal quality of the initial AlN layer affects the increase in the VDBV of the AlGaN/GaN HEMTs on Si substrates.